Strategi Pemasaran UMKM Berbasis Marketing Mix dan Analisis SWOT: Studi Kasus Es Teh Kampung Solo - Rodifah Rodifah; Abdurrahim Fadhl; Firda Ulinnuha; Bagus Maulana; Tajudin M.M. (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2026)
The results of the study show that pricing strategy contributes dominantly to increasing sales, but the lack of digital promotion causes limited market reach. Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in driving national economic development and providing employment. However, in facing an increasingly competitive market, MSMEs need to implement efficient marketing strategies to ensure sustainability and sustainable growth. This community service activity aims to provide knowledge and assistance to Indonesian Es Teh MSMEs regarding the implementation of flexible marketing strategies, both through digital and traditional channels. The activity took place at the Es Teh Kampung Solo outlet in Kramatwatu Square. The methods used included counseling, training, and assessment of marketing strategy implementation, with a primary focus on optimizing social media as an interactive and competitive digital promotional tool. The results of this activity demonstrated a significant increase in MSMEs' understanding of strategic marketing planning, promotional innovation, and the use of digital platforms to expand market reach. Thus, it is hoped that digital-based marketing strategies can strengthen the competitiveness and sustainability of MSMEs. This activity is expected to contribute to increasing the competitiveness and sales volume of the Kampung Solo Es Teh MSME in a sustainable manner through the implementation of a modern marketing approach that is responsive to technological changes.